2020
DOI: 10.1007/s11092-020-09336-6
|View full text |Cite
|
Sign up to set email alerts
|

Online vs. offline course evaluation revisited: testing the invariance of a course evaluation questionnaire using a multigroup confirmatory factor analysis framework

Abstract: Survey-based formats of assessing teaching quality in higher education are widely used and will likely continue to be used by higher education institutions around the world as various global trends contributing to their widespread use further evolve. Although the use of mobile devices for course evaluation continues to grow, there remain some unresolved aspects of the classic paper and web-based modes of evaluation. In the current study, the multigroup confirmatory factor analysis approach (MGCFA), an accepted… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 41 publications
0
4
0
1
Order By: Relevance
“…Despite the significant decrease in return rates, several studies reported that online collection methods did not adversely affect average course rating scores across programs and faculty (Avery et al, 2006;Dommeyer et al, 2004;Fogarty et al, 2013;Liegle & McDonald, 2005;Perrett, 2013;Laupper et al, 2020). In many studies the reported drop in response rates occurred immediately following the transition to online methods (Avery et al, 2006;Fogarty et al, 2013;Kuch & Roberts, 2018;Liegle & McDonald, 2005).…”
Section: Impact On Response Ratesmentioning
confidence: 99%
“…Despite the significant decrease in return rates, several studies reported that online collection methods did not adversely affect average course rating scores across programs and faculty (Avery et al, 2006;Dommeyer et al, 2004;Fogarty et al, 2013;Liegle & McDonald, 2005;Perrett, 2013;Laupper et al, 2020). In many studies the reported drop in response rates occurred immediately following the transition to online methods (Avery et al, 2006;Fogarty et al, 2013;Kuch & Roberts, 2018;Liegle & McDonald, 2005).…”
Section: Impact On Response Ratesmentioning
confidence: 99%
“…The study could be improved by increasing the number of male participants and of other, non-heterosexual orientations. This having been said, the use of offline and online questionnaires does not affect the quality of the results [ 44 ]. Another limitation concerns the variables used in the study.…”
Section: Discussionmentioning
confidence: 99%
“…Little or no influence of SRI delivery mode (paper-based vs electronic/online) on overall SRI scores was found in three studies (Laupper et al, 2020;Risquez et al, 2015;Treischl & Wolbring, 2017). In contrast, Fogarty et al (2013) found significantly lower evaluation scores with web-based SRI administration.…”
Section: Types Of Biasmentioning
confidence: 92%